Penerapan Sistem Informasi Tanda Tangan Digital Melalui E-Certificate - Moch. Mahsun; Wardatuz Sobri; Bayu Widiyanto; Taqwa Nur Ibad (Program Study Office Adminstrative of Akademi Komunitas Teknologi Syarifuddin Lumajang, 2020)
Education can be interpreted as a means of transportation of communication, skills, and cultural education both inside and outside lectures. On the other hand, higher education information systems can be defined as media supporting the transformation process of knowledge communication in educational organizations such as types of universities. A system consisting of several parts that operate together and are interconnected to achieve several missions desired by management. The focus of the problem raised is information systems in the form of digital hands through integrated information system services. The signature guarantees the integrity and source of a message, the signature is authentic (authentic), not easy to write / imitate and the message can also work as evidence. This research uses research and development (R&D) methods that are used to produce certain products through the development process and the effectiveness of the product itself is tested.